Pengembangan Lembar Kerja Siswa Terintegrasi dengan Pendekatan Matematika Realistik pada Materi Bilangan di Kelas 1 Sekolah Dasar - Yosi Arianita; Agus Susanta; Irwan Koto (UNIB Press, 2023)
This study aims to develop LKS with integrated realistic mathematics. The development model used is a procedural model of Borg & Gall with six stages, namely (1) Preliminary Study (Research and information collecting), (2) Planning (Planning), (3) Development of Initial Product Design (Develop Preliminary form of Product). (4) Preminary Field Testing. The research was carried out at SD Negeri 01 Pendopo and the subjects of the research were 28 students in class IA. The result of this study is an integrated LKS of realistic mathematics on valid number material based on the assessment of material experts, linguists, and media experts. The feasibility value of the material expert is 0.9833, the feasibility of the linguist is 0.958, while the feasibility of the media expert is 0.8. And the student response was 9.6% while the teacher gave a positive response. These results showed that LKS with realistic mathematical integration was feasible and received a positive response.